2020
DOI: 10.3389/fphys.2020.574851
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Dietary Sugars on the Development and Fecundity of Harmonia axyridis

Abstract: The aim of this study was to screen synergistic substances included in existing artificial feeds in order to improve the fertility and survival rate of Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae), an efficient pest predator. To this end, we analyzed the potential effects of glucose and trehalose on the growth, development, and reproduction of H. axyridis and evaluated the effect of three different artificial feeds on the energy stress of H. axyridis. The artificial diets contained fresh pork liver, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 83 publications
2
22
1
Order By: Relevance
“… Cambron et al (2019) suggested that caterpillars exposed to HFD eat less and might feel “sick” due to consuming high amounts of lipids in the diet, resulting in smaller individuals. Similar to our results on HSD, increased body weight has been reported in larvae and pupa of the predator Harmonia axyridis (Coleoptera: Coccinellidae) ( Li et al, 2020 ), adult Drosophila ( Morris et al, 2012 ; Rovenko et al, 2015a ), and the mosquito Ae. aegypti ( van Schoor et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“… Cambron et al (2019) suggested that caterpillars exposed to HFD eat less and might feel “sick” due to consuming high amounts of lipids in the diet, resulting in smaller individuals. Similar to our results on HSD, increased body weight has been reported in larvae and pupa of the predator Harmonia axyridis (Coleoptera: Coccinellidae) ( Li et al, 2020 ), adult Drosophila ( Morris et al, 2012 ; Rovenko et al, 2015a ), and the mosquito Ae. aegypti ( van Schoor et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that decreased food consumption may not be the reason for the coincidental developmental delay. On the other hand, HSDs have been reported to accelerate larval development in Drosophila ( Tatum and Beadle, 1939 ), H. axyridis ( Li et al, 2020 ), and Ae . aegypti ( van Schoor et al, 2020 ) while developmental delays in response to HSD with excessive levels of carbohydrates have been reported ( Rovenko et al, 2015a , b ; van Schoor et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Determining these parameters with respect to phenological stage confirmed poor response by the first three instars as reported earlier 59 , 74 , whereas increased foraging performance by final instar and adult H. axyridis (especially female when compared with male) 24 , 45 , 52 suggesting H. axyridis may provide better biocontrol efficiency at later stages, plausibly owing to better searching efficiencies. The 4th instar requires large meals to attain the required weight for pupation 75 and adult predators have to prepare for reproduction 56 and other functions related to egg maturation or fertilization 76 . Our results of greater predation by the 4th instar and female H. axyridis are supported by previous reports investigating the functional response of coccinellids, namely Adalia tetraspilota (Hope), Hippodamia variegata (Goeze), Harmonia dimidiata (Fab.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Pan et al (2014) fed first instar nymphs of BPH with standard artificial feed and amino acid-deficient artificial feed, and found that the development period was significantly shortened, indicating that growth is accelerated when their diets are poor in amino acids. The larval and pupal stages of Harmonia axyridis were significantly prolonged after feeding with multiple artificial feed formulations ( Li et al, 2020 ). Proteins and carbohydrates are the two most important basic nutrients for insect growth and development, and provide the necessary amino acids and energy for insect growth and development.…”
Section: Discussionmentioning
confidence: 99%